2019
DOI: 10.1111/jgh.14596
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of celiac disease in South African patients with type 1 diabetes mellitus: Results from the Durban Diabetes and Celiac Disease Study

Abstract: Background and Aim The aim of this study was to assess the prevalence and characteristics of celiac disease (CD) in all patients with type 1 diabetes mellitus attending a tertiary adult diabetes clinic in Durban, South Africa. Methods This was a cross‐sectional observational study that screened 202 patients; of these, 56.4% were African (Black), 31.7% Asian Indian, 4.5% White, and 7.4% mixed race. Demographic data, symptoms, and anthropometry were documented. Blood tests included anti‐tissue transglutaminase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(86 reference statements)
3
5
0
Order By: Relevance
“…Alternatively, a lack of awareness and the false belief that CD does not occur in black ethnic groups may lead to a lowered detection rate and therefore a low prevalence of diagnosed CD in sub-Saharan Africa. This is supported by Paruk et al, [14] who reported a similar prevalence of CD in SA black patients with type 1 diabetes as studies from Western countries. Poor access to serological screening tests and confirmatory endoscopy may have an additional effect, as not all healthcare centres are well resourced or adequately equipped in our setting.…”
Section: Researchsupporting
confidence: 76%
“…Alternatively, a lack of awareness and the false belief that CD does not occur in black ethnic groups may lead to a lowered detection rate and therefore a low prevalence of diagnosed CD in sub-Saharan Africa. This is supported by Paruk et al, [14] who reported a similar prevalence of CD in SA black patients with type 1 diabetes as studies from Western countries. Poor access to serological screening tests and confirmatory endoscopy may have an additional effect, as not all healthcare centres are well resourced or adequately equipped in our setting.…”
Section: Researchsupporting
confidence: 76%
“…This is much lower than the reported prevalence of 44.5% and 32.2% in paediatric and adult patients, respectively in Durban, South Africa. [17,18] This may occur as a result of different antibody testing. Serology was positive based on either tTG-A or EMA, while in the adult study patients' serology was deemed positive if any of the three antibodies were positive (tTG-A, EMA, anti-gliadin antibodies [AGA]).…”
Section: Discussionmentioning
confidence: 99%
“…Serology was positive based on either tTG-A or EMA, while in the adult study patients' serology was deemed positive if any of the three antibodies were positive (tTG-A, EMA, anti-gliadin antibodies [AGA]). [17,18] EMA and tTG-A both have a specificity and sensitivity >90% in symptomatic individuals (Table 3). [3][4][5]21] When used as screening tests, however, their positive predictive value is lower, in the range of 70 -83%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation is associated with the whole course of T2DM, and it plays an important role in the development and progression of DR. Activation of B cells contributed to the development of DM in recent years [ 21 23 ]. However, the immune response mediated by B cells has been rarely reported in the DR patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%